Exploring the Implementation of Effective Virtual Counseling: A Systematic Review - Mohammadkashi, Mahta; Madani, Yaser; Salehi, Keyvan (KMAN Counseling & Psychology Nexus, 2025)
Virtual counseling, as a new approach in the field of counseling services, is gradually replacing face-to-face counseling due to its accessibility and the possibility of communication at any time. However, the client experience in this modality may differ from that of traditional in-person counseling. In this documentary study using a systematic review, key facilitators and barriers influencing the implementation of virtual counseling processes were examined. A total of 860 documents were retrieved from domestic databases such as Noormags, IranDoc, Civilica, ElmNet, and Human Sciences Portal within the time span of 2019 to 2023. Based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist indicators, 12 documents were selected for review. Additionally, 540 documents were retrieved from international databases including ERIC, Sage, Elsevier, Scopus, and Taylor & Francis from 2000 to 2024, from which 28 documents were selected for analysis using the PRISMA checklist. Data analysis was conducted using the Altheide method. The findings revealed four facilitating factors, including technological infrastructure, counselor training and competence, client engagement strategies, and organizational support, as well as four inhibiting factors, namely technological barriers, concerns about privacy and confidentiality, client resistance, and lack of standardization.